2019
DOI: 10.3390/ijms20174256
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Fatty Acids and Neurodegenerative Diseases: New Evidence in Clinical Trials

Abstract: A nutritional approach could be a promising strategy to prevent or slow the progression of neurodegenerative diseases such as Parkinson’s and Alzheimer’s disease, since there is no effective therapy for these diseases so far. The beneficial effects of omega-3 fatty acids are now well established by a plethora of studies through their involvement in multiple biochemical functions, including synthesis of anti-inflammatory mediators, cell membrane fluidity, intracellular signaling, and gene expression. This syste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
87
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(88 citation statements)
references
References 79 publications
0
87
0
1
Order By: Relevance
“…Such a modification in the membrane structure and fluidity, and consequently in the membrane thickness directly affects the degree of exposure of membrane proteins on the cell surface, influences accessibility of reactive chemical groups and induces conformational changes of the proteins. Thus, the interrelated physical and biochemical events in plasma membranes may have an impact on membrane functions, signaling, neurotransmission, permeability, and other cellular events [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such a modification in the membrane structure and fluidity, and consequently in the membrane thickness directly affects the degree of exposure of membrane proteins on the cell surface, influences accessibility of reactive chemical groups and induces conformational changes of the proteins. Thus, the interrelated physical and biochemical events in plasma membranes may have an impact on membrane functions, signaling, neurotransmission, permeability, and other cellular events [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…They are components of neuronal membranes and have a main role in neurotransmission, neuronal development and function [105]. Two of the main omega-3 FAs are docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) and it has been demonstrated that supplementation with omega-3 FAs has beneficial effects in several neurodegenerative and neuropsychiatric disorders such as Parkinson´s and Alzheimer´s diseases, depression, bipolar disorder, anxiety, and schizophrenia [106,107]. These omega-3 FAs are also known to have anti-inflammatory effects [108,109].…”
Section: Omega-3 Fatty Acids Prevent Inflammationmentioning
confidence: 99%
“…Actually, in the last few years, numerous observational studies showed an association between a diet rich in PUFAs and a lower risk of PD. Moreover, dietary treatments with PUFAs have shown to decrease the inflammatory status of these NDs and decrease depressive symptoms, among others [ 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%